Optimizing Digital Marketing in Strengthening Tourist Destination Marketing: A Conceptual Study in the Tourism Sector of Jambi Province - Gupron Gupron; M. Ridho Mahaputra; Andri Yandi (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
Digital transformation has shifted the marketing paradigm of tourist destinations through the utilization of various digital platforms capable of reaching tourists more broadly and interactively. Nevertheless, the implementation of digital marketing in the tourism sector in Jambi Province still faces challenges in optimizing its impact on strengthening destination marketing. On the other hand, most previous studies tend to examine the effect of digital marketing on brand awareness, electronic word of mouth (e-WOM), or visit intention partially, while studies that integrate these three aspects within a single conceptual framework in the context of regional tourist destinations remain relatively limited. This study aims to develop a conceptual model for optimizing digital marketing in strengthening tourist destination marketing through enhancing brand awareness, e-WOM, and visit intention in the tourism sector of Jambi Province. The research employs a qualitative approach using a conceptual review method through systematic literature study of relevant scholarly articles, books, and publications on digital marketing and tourist destination marketing. The findings indicate that an integrated digital marketing strategy has the potential to build destination brand awareness, encourage the dissemination of positive information through e-WOM, and increase tourist visit intention. These three constructs are interrelated and form a mechanism that strengthens the effectiveness of tourist destination marketing. The novelty of this research lies in the development of a conceptual model that integrates brand awareness, e-WOM, and visit intention as primary mechanisms in optimizing digital marketing within the context of the tourism sector in Jambi Province, thereby serving as a foundation for empirical research as well as for formulating digital-based destination marketing strategies.